Chinese Commercial Banks and the Global Financial Crisis: What was their Risk Management before the Crisis? How do they Change afterwards? - WANG, Yiqiao (2011)
Risk management plays a crucial role in the profit-earning activities of commercial banks. It contains three major types and each type requires different risk measurement tools. A successful and sustainable risk management system needs the enterprise-wide participation of employees and integration of all different components together with a deep-rooted culture. Moreover, risk management in commercial banks has the most authoritative practical guidelines—Basel Accords, which providing minimum capital requirements, risk measurement methodologies, supervision requirements, market disciplines, etc.